Integrated-Power-Control-Strategy-Based Electrolytic Capacitor-Less Back-to-Back Converter for Variable Frequency Speed Control System - Bao, Danyang; Pan, Xuewei; Wang, Yi; Huang, Hao; Wu, Bingyi (IEEE transactions on industrial electronics (1982), 2020)
This article presents an integrated power control strategy (IPCS) for a variable frequency speed regulation system, which consists of a back-to-back converter and a small film dc-link capacitor. Due to the lack of large-capacity energy storage components in the dc bus, there is a strong power coupling between the rectifier and the inverter. The dynamic response is limited and dc-link voltage oscillates because the traditional method controls rectification and inversion separately. The IPCS is proposed to achieve dynamic balance of the system power through synchronous control of the rectifier and inverter. High conversion efficiency guarantees the power balance of the rectifier and inverter meanwhile reduces the dc bus voltage ripple. To further reduce the dc-link voltage ripple and maintain the stability of the dc-link voltage under step changes of load, a virtual inertia control method is proposed, which consists of a virtual resistance control block and a virtual capacitor control block. As a result, the dc-link voltage ripple and the total harmonic distortion of the dc-link current can be improved. Simulations and experimental results are given to provide further validation of the proposed IPCS under different operating scenarios.